Corporate Governance Attributes and the Likelihood of Fraud on Financial Statements of Listed Deposit Money Banks in Nigeria - Chukwuma, Obumneme Eugene; Abdulkarim, Shaibu Alhassan; Abdullahi, Musa Abdullahi (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
Frequent occurrences of banks winding up and merging in Nigeria have cast doubt on the adequacy of existing corporate governance mechanisms, which necessitates an investigation into how governance attributes influence the integrity of financial reporting. Therefore, this study examined the effect of corporate governance attributes on the financial statement fraud likelihood of listed deposit money banks in Nigeria for the period 2014-2023. An ex-post facto research design was adopted for the study. This study utilized census sampling techniques to take all 15 deposit money banks listed on the Nigerian Exchange Group (NGX). The data used in this study were secondary, derived from the annual reports and accounts of deposit money banks listed in Nigeria. The study used logistic regression to analyze data. The logistic regression results revealed that independent directors, audit committee independence, and financial expertise have a significant effect on the financial statement fraud likelihood of listed deposit money banks in Nigeria. The board size and gender diversity have no significant effect on financial statement fraud likelihood. The study concluded that independent directors, audit committee independence, and financial expertise reduce the likelihood of financial statement fraud, while board size and gender diversity have no influence on the likelihood of financial statement fraud. The study recommended that deposit money banks in Nigeria should focus on appointing independent directors and audit committee members with strong financial expertise. Although board size and gender diversity may not directly influence fraud risk, active involvement of all directors in fraud prevention is essential.